International consensus on allergy immunotherapy - Jutel, Marek; Pfaar, Oliver (The journal of allergy and clinical immunology, 2015)
Allergen immunotherapy (AIT) has been used to treat allergic disease since the early 1900s. Despite numerous clinical trials and meta-analyses proving AIT efficacious, it remains underused and is estimated to be used in less than 10% of patients with allergic rhinitis or asthma worldwide. In addition, there are large differences between regions, which are not only due to socioeconomic status. There is practically no controversy about the use of AIT in the treatment of allergic rhinitis and allergic asthma, but for atopic dermatitis or food allergy, the indications for AIT are not well defined. The elaboration of a wider consensus is of utmost importance because AIT is the only treatment that can change the course of allergic disease by preventing the development of asthma and new allergen sensitizations and by inducing allergen-specific immune tolerance. Safer and more effective AIT strategies are being continuously developed both through elaboration of new allergen preparations and adjuvants and alternate routes of administration. A number of guidelines, consensus documents, or both are available on both the international and national levels. The international community of allergy specialists recognizes the need to develop a comprehensive consensus report to harmonize, disseminate, and implement the best AIT practice. Consequently, the International Collaboration in Asthma, Allergy and Immunology, formed by the European Academy of Allergy and Clinical Immunology; the American Academy of Allergy, Asthma & Immunology; the American College of Allergy, Asthma & Immunology; and the World Allergy Organization, has decided to issue an international consensus on AIT.
Gesehen am 01.03.2018